PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, PROFITABILITAS, STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2013-2016) - Christina D C M, 14.05.52.0038; Nurhayati, Ida (Students Journal of Accounting and Banking, 2018)
This study aimed to examines and analyzes the influence of institutional ownership, managerial ownership, profitability, capital structure and growth company to the firm value on manufacturing companies listed in indonesia stock exchange in the period 2013-2016. The population of this research are manufacturing companies listed in indonesia stock exchange. The study uses secondar data such as realization report 2013 until 2016 and obtained as many 210 companies. The technique of data analysis is used multiple regression analysis with interation method. The results of this study shows that profitability has a positive influence on firm value and Growth has negatife influence on firm value. While Institustional ownership does not affect on firm value. Managerial ownership has a negative influence on firm value. And Capital structure does not affect on firm value.Keywords : Manufacturing industry, institutional ownership, managerial ownership, profitabilty, capital structure, growth company, firm value